Effect of leg stiffness characteristics on take-off motion during bounding - Kariyama, Y.; Zushi, K. (Japan Journal of Physical Education, Health and Sport Sciences, 2016)
In the present study, we aimed to (1) clarify the relationship between stiffness and take-off leg motion during bounding and (2) append the information gathered from the study to a hierarchical training model (Kariyama and Zushi 2013, 2015). Seventeen male track and field athletes (sprinters, jumpers, and decathletes) performed bounding. Jumping motions in the sagittal plane (300 Hz) and ground reaction force data (1,000 Hz) were recorded. Stiffness was calculated using the spring-mass model, and the kinematic and kinetic variables of both the take-off leg and swing leg were calculated. We found correlations between stiffness and the following parameters: vertical ground reaction force impulse during the late phase (r=-0.488), distance between the center of gravity of the body (CG) and the toe at touch down (r=-0.760), hip-toe distance at touch down and at toe off (r=-0.568 and -0.472, respectively), range of flexion at the hip joint angle (r=-0.517), range of extension at the knee joint angle (r=-0.484), negative joint work and relative work at the hip joint (r=-0.462 and -0.511, respectively), positive joint work and relative work at the knee joint (r=-0.619 and -0.534, respectively), swing-leg angle at touch down (r=-0.755), and swing-leg vertical impulse during the late phase (r=-0.535). The results we obtained suggest that take-off motion in bounding is affected by stiffness characteristics, although jump distance is not affected by stiffness (Kariyama and Zushi 2013, 2015). Previous studies (Kariyama and Zushi 2013, 2015) indicated that stiffness in bounding is affected by stiffness in rebound jumping. On the basis of our results and those of previous studies, take-off motion correlated with stiffness in bounding could be affected by rebound jump stiffness. Therefore, an understanding of the characteristics of stiffness in rebound jumping is important for training that changes the above-mentioned take-off motion in bounding.